Presentations for Post COP28 Priorities for Advancing Food Systems Transformation - Mukherji, Aditi; Swinnen, Johan; Zhang, Qingfeng (International Food Policy Research Institute, 2024)
Held in 2023, the planet’s hottest year on record, COP28 has been heralded for its strong focus on food systems, which are simultaneously threatened by and contribute to climate change. The COP28 Declaration on Sustainable Agriculture, Resilient Food Systems and Climate Action, albeit non-binding, but endorsed by almost 160 countries, emphasizes the transformative potential of agriculture and food systems in responding to climate change and ensuring global food security.